(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To build and validate a nursing care protocol to adult patients who suffered burns in a public hospital in the North region of Brazil and evaluate its applicability. Method: Methodological study that followed the steps: construction of the instrument; content validation using the Appraisal of Guidelines for Research & Evaluation II (AGREE II) assessment tool; and applicability analysis with a semi-structured questionnaire with the nursing team and by agreement and Kappa test. Results: In the situational diagnosis stage, the protocol was elaborated based on the literature review and validated by the specialists through the AGREE II instrument with a general content validity index value of 0.93 and through the analysis of applicability with Kappa test analysis, obtaining a value of 0.81, with almost perfect agreement. Conclusion: The protocol was structured with quality to guide the nursing team in assisting burned patients. Therefore, its use is indicated.